Those terrible toy-breakers - McPhail, David, 1940- (New York : Parents Magazine Press, 1980)
Walter and Bernie set a trap for the lion, tiger, and elephant who break Walter's toys that are left outside overnight.
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Toys; Toys; Animals; Animals; Fiction; Fiction